The “Manic Pixie Dream Girl of the Synth-Pop World” and Her “Baby Doll Lisp”: Grimes and the Disabling Logics of the Feminization and Infantilization of Lisping - Holmes, Jessica A. (Journal of Popular Music Studies, 2019)
Audible in speech and song, electro-pop singer Grimes’s so-called “baby doll” lisp generates endless buzz online, ranging from light-hearted adoration, to infantilization, to sexual fetish and even to ableist, misogynist anti-fandom. This article uses the reception of her lisp to build an intersectional theory of lisping across its medical and socio-cultural constructions, bridging work in disability studies, dysfluency studies, voice studies, and popular music studies in the process. I situate the slippage between adoring, infantilizing, fetishistic, and violent characterizations of Grimes’s lisp as reflective of the infantilization of “communicative disorders” in speech language pathology, and the dysfunction associated with feminine coded-speech patterns (e.g. vocal fry and up talk) in the popular imaginary. Lisping is profitably understood as an audible form of “liminal” difference relative to visible physical disabilities (St. Pierre), and to certain ableist, gendered, and racialized conceptions of normative vocality. Ultimately, in the English-speaking world, the lisp is symbolically-coded feminine while exceeding the norms of female vocality, thereby giving rise to a polarizing set of associations that work against female authority and, by extension in Grimes’s case, female musical authorship. Grimes’s reception thus offers a valuable case study for interrogating how misogynist fantasies regarding femininity are thought localized in the female voice, and the symbolic ties between disability and femininity.
Publisher: University of California Press

Avant-propos. Pour des musicien·ne·s organiques ? - McKinley, Maxime (Circuit, 2018)
Publisher: Circuit, musiques contemporaines
Keywords: Inclure l'avant-propos ?

"The Canadian Inhabitants are Remarkably Fond of Dancing": Reading the African Musicians in George Heriot's Minuet of the Canadians (1807) - Nelson, Charmaine A. (Towards an African Canadian Art History: Art, Memory, and Resistance, 2018)
Towards an African Art History: Art, Memory, and Resistance, is the first book to consoloidate the field of African Canadian Art History. In this book, Charmaine A. Nelson and her colleagues–a group of established and up-and-coming artists, scholars, and cultural critics–argue for an African Canadian Art History that can simultaneously examine the artistic contributions of black Canadian artists within their unique historical contexts, critique the colonial representation of black subjects by white artists, and contest the customary racial homogeneity of Canadian Art History. Challenging the traditional notions of artistic value, this groundbreaking book examines art, artists, and visual and material culture from the eighteenth century to the present, analyzing "high," "low," and popular art across various media, with a focus to offer a new perspective on Canadian Art History–an African Canadian Art History

Le hip-hop avec des gants blancs - Néméh-Nombré, Philippe (Liberté, 2018)
Réflexion sur la dépolitisation et l’éclaircissement du hip-hop lors de son passage dans la culture de masse.

“Come One, Come All”: Blackface Minstrelsy as a Canadian Tradition and Early Form of Popular Culture - Thompson, Cheryl (Towards an African Canadian Art History: Art, Memory, and Resistance, 2018)
Towards an African Art History: Art, Memory, and Resistance, is the first book to consoloidate the field of African Canadian Art History. In this book, Charmaine A. Nelson and her colleagues–a group of established and up-and-coming artists, scholars, and cultural critics–argue for an African Canadian Art History that can simultaneously examine the artistic contributions of black Canadian artists within their unique historical contexts, critique the colonial representation of black subjects by white artists, and contest the customary racial homogeneity of Canadian Art History. Challenging the traditional notions of artistic value, this groundbreaking book examines art, artists, and visual and material culture from the eighteenth century to the present, analyzing "high," "low," and popular art across various media, with a focus to offer a new perspective on Canadian Art History–an African Canadian Art History

Les chemins de ma liberté - Simard, Nathalie (Éditions des Intouchables, 2015)

Le Lunatique, « Le temps du changement » : Intimidation, ostracisme et homophobie dans le milieu hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Le tout premier livre monographique et scientifique axé sur la culture Hip-Hop au Québec, rédigé par Kapois Lamort, historien spécialiste diplômé de l’Université du Québec à Montréal ( UQAM); cet ouvrage retrace les 35 ans d’existence du H.I.P.H.O.P. à travers la société québécoise de 1979 à 2015

Choral, Public and Private Listener Responses to Hildegard Westerkamp's École - McCartney, Andra; McCarthy, Marta (Music and Arts in Action, 2012)
Hildegard Westerkamp's (1990) composition École Polytechnique is an artistic response to one of Canada's most profoundly disturbing mass murders, the 1989 slaying of fourteen women in Montreal, Quebec. Using the theoretical model, derived from Haraway, of the cyborg body, and analyzing the import of the mixed media (voices, instruments and electroacoustic tape) incorporated in the music, the authors examine the impact this work has had on some of those who have heard it and performed it, based on the responses of choristers and listeners in several studies. The authors explored how those who engaged significantly with the music, (including those who had no personal association with the actual events of the 1989 massacre), were able to make relevant connections between their own experience and the composition itself, embrace these connections and their disturbing resonances, and thereby experience meaningful emotional growth.
Accepted: 2012-11-14T10:25:30Z Publisher: University of Exeter